The explosion in cryptocurrencies: A black hole analogy - Antonis Ballis; Konstantinos Drakos (Financial Innovation, 2021)
Using an analogy between finance and astrophysics, this study aims to investigate whether there exists a mechanism that can describe the explosive increase in the number of traded cryptocurrencies and the cryptocurrency market in general. In physics, the Schwarzschild radius indicates that black holes are constantly expanding because of their mass increase. Enriching this analogy, we consider the cryptocurrency market as a self-gravitational body whose mass is denoted by (1) the number of traded cryptocurrencies and (2) in terms of increasing market capitalization for a given number of traded cryptocurrencies. By analyzing weekly snapshot data of all traded cryptocurrencies from January 4, 2009, to June 14, 2020, we find evidence that the above-mentioned mechanism exists. The results clearly indicate the self-gravitational property of the cryptocurrency market, which is direct evidence toward the hypothesis that the changes in the traded cryptocurrencies are a positive function of the previous period's number of traded cryptocurrencies.
Keywords: G14; G15; G23; 650; Bitcoin; Cryptocurrencies; Econophysics; Negative specific heat; Thermodynamic disequilibrium